Innovation Strategies to Support Good Mining Practices and Competitiveness: A Study at PT J Resources Bolaang Mongondow - Saragih, Andreas Cahya U.R.P.; Riyadi, Selamet; Sosidah; Rohman, Abdul (International Journal of Environmental, Sustainability, and Social Science, 2026)
The gold mining industry faces increasing pressure to not only achieve high financial performance but also ensure responsible and sustainable mining practices. The concept of Good Mining Practice (GMP) requires companies to integrate technical compliance, occupational safety, environmental protection, and social responsibility throughout the mining business cycle. In this context, innovation strategies play a crucial role as a driver of change towards safer, more efficient, and more competitive mining operations. This article aims to critically review the literature on innovation strategy, GMP, and corporate competitiveness, and synthesize how the two can strengthen each other, with a contextual focus on PT J Resources Bolaang Mongondow (JRBM), one of the gold mining companies in Indonesia. The method used is a literature review of scientific articles, books, and policy documents related to innovation strategy, mining management, and sustainability. The results of the study indicate that innovation strategies aligned with GMP generally take the form of: (1) technological and process innovation to increase efficiency and reduce environmental impact; (2) innovation in safety and risk management systems; (3) social innovation through strengthening relationships with communities and stakeholders; and (4) managerial innovation and business models that make sustainability a source of competitive advantage, not simply a regulatory obligation. For a gold mining company like PT J Resources Bolaang Mongondow, the combination of exploitation innovation (continuous improvement of existing processes) and exploration innovation (development of new technology- and social-based approaches) has the potential to strengthen its license to operate, reputation, and long-term competitiveness.